Optimum coupling and multimode excitation of traveling‐waves in a whole‐body 9.4T scanner. Issue 6 (10th July 2012) - Geschewski, Frank H.; Brenner, Daniel; Felder, Jörg; Jon Shah, N.
Abstract: Given the absence of a body coil, the radio frequency screen of a whole‐body 9.4T magnetic resonance imaging scanner can be used as a circular waveguide. In the unloaded case, the screen allows propagation of the dominant TE11 ‐ as well as the TM01 ‐mode. In the first part of this study, the optimum coupling of a circular polarized TE11 ‐mode was determined empirically for excitation and reception with a rectangular patch antenna. Employing full‐wave simulations, two simulation models and two phantoms, different patch positions were tested to find the optimum position with respect to coupled power and homogenous excitation field. The best simulation results were validated with measurements. The second part of this study describes the design and measurements of a multimode excitation device. Using the parallel transmit system of the MR scanner, all propagable traveling wave modes could be excited and detected independently. The performance of the multimode device related to field of view, B 1 + ‐efficiency and radio frequency shimming was assessed by phantom measurements. Initial results show that three modes are sufficient to homogeneously excite regions of interest at 9.4 T. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.